Lanadelumab for prevention of attacks of non-histaminergic normal C1 inhibitor angioedema: results from the randomized, double-blind CASPIAN Study and CASPIAN open-label extension - Riedl, Marc A.; Staubach, Petra; Farkas, Henriette; Zanichelli, Andrea; Ren, Hong; Nurse, Christina; Andresen, Irmgard; Juethner, Salomé; Yu, Ming; Zhang, Jingmei (Frontiers in Immunology, 2025)
BackgroundRandomized controlled trial data for non-histaminergic normal C1 inhibitor (nC1INH) angioedema prevention are lacking.MethodsPatients aged ≥12 years with investigator-confirmed non-histaminergic nC1INH angioedema were enrolled in phase III, multicenter, randomized, placebo-controlled, double-blind CASPIAN Study (NCT04206605). Patients with ≥1 investigator-confirmed angioedema attack/4 weeks during observation period were randomized 2:1 to lanadelumab 300 mg every 2 weeks or placebo. Primary efficacy outcome was investigator-confirmed angioedema attack number during the 26-week treatment period. Safety was analyzed as treatment-emergent adverse events (TEAEs). After completing the treatment period, patients could roll over to CASPIAN open-label extension (CASPIAN OLE; NCT04444895) for an additional 26-week lanadelumab treatment to assess long-term safety and efficacy.ResultsA total of 77 patients (mean ± SD age of 42.8 ± 12.9 years, 80.5% women, 88.3% White) were enrolled (lanadelumab, 50; placebo, 27). Primary efficacy outcome was not different with lanadelumab versus placebo (1.82 vs. 1.78 attacks/month; rate ratio, 1.02; p=0.90), with attack rate reduction from baseline in both groups. Subgroups meeting a clinical definition of HAE [known mutations (n=5) or family history and unknown mutations (n=13)] showed positive attack rate reduction trend with lanadelumab versus placebo. Angioedema attack rate reduction with lanadelumab was observed in CASPIAN OLE. In both studies, all treatment-related TEAEs were non-serious, and most were non-severe; most frequent treatment-related TEAEs were similar to those previously reported in lanadelumab clinical trials.ConclusionIn patients with non-histaminergic nC1INH angioedema, lanadelumab safety was consistent with previous studies; efficacy remained inconclusive due to unmet CASPIAN primary endpoint. Overall results suggest potential clinical benefit in symptom control.Clinical trial registrationhttps://www.clinicaltrials.gov/, identifiers NCT04206605, NCT04444895.